Élaboration d’une formation à l’affilage des couteaux : Le travail d’un collectif, travailleurs et ergonomes - Nicole Vézina; Johanne Prévost; Alain Lajoie; Yves Beauchamp (Perspectives Interdisciplinaires sur le Travail et la Santé)
A number of ergonomic interventions in pig slaughterhouses and pork processing plants revealed the importance of properly sharpened knives for workers engaged in butchering operations. A blunt knife increases a number of risk factors that may lead to musculo-skeletal problems. Given the lack of training in knife sharpening, an ergonomic study was carried out in six plants in order to develop training content. The research required intensive participation by 18 worker-experts. Knowledge and expertise was pooled at a series of meetings of different types. The paper discusses the elements of knowledge that participants agreed should be included in the training, and those that were the subject of debate. It also examines the methods used to promote discussion and identify the key elements underlying differences of opinion.